Kenya National Climate Smart Agriculture (CSA) Monitoring and Evaluation Framework. [Module 2] - Alliance of Bioversity International and CIAT; Ministry of Agriculture and Livestock Development, Kenya; Climate Smart Agriculture Multi-Stakeholder Platform (2023)
The Initiative for Climate Action Transparency (ICAT) project is a collaborative effort between the Alliance of Bioversity International and CIAT, and the Ministry of Agriculture and Livestock Development in Kenya. The project aims to strengthen the capacity of the agriculture sector to implement, monitor, and report adaptation actions in a transparent manner at both national and county levels. To achieve this, the project has developed three training modules that will help to operationalize the CSA reporting tool for the agriculture sector. This second module will increase stakeholders’ knowledge on the need for a national climate smart agriculture monitoring and evaluation framework to track, report, and increase transparency in the reporting of adaptation actions.